A Study Literature of Interest Rates and Islamic Monetary Policy - Mala, Chajar Matari Fath (The Es Economics and Entrepreneurship, 2023)
This paper provides a comprehensive analysis of the existing literature about contemporary Islamic monetary policy and its implementation through interest rates in the context of monetary policy. Upon conducting a comprehensive examination of the pertinent literature, it becomes evident that numerous conventional monetary policy instruments can be suitably modified and employed within the framework of Islamic monetary policy. Using interest rates as a monetary policy tool has been observed to directly impact injustice, including social unfairness, widespread corruption, and manipulation by global financial institutions that governments and authorities support. The current global financial crisis exemplified this. This study aims to analyze the several alternatives to interest rates utilized in Islamic monetary policy tools while also conducting a literature analysis on Islamic monetary policy.